2017
DOI: 10.1371/journal.pone.0170331
|View full text |Cite
|
Sign up to set email alerts
|

Anodal Transcranial Direct Current Stimulation Shows Minimal, Measure-Specific Effects on Dynamic Postural Control in Young and Older Adults: A Double Blind, Sham-Controlled Study

Abstract: We investigated whether stimulating the cerebellum and primary motor cortex (M1) using transcranial direct current stimulation (tDCS) could affect postural control in young and older adults. tDCS was employed using a double-blind, sham-controlled design, in which young (aged 18–35) and older adults (aged 65+) were assessed over three sessions, one for each stimulatory condition–M1, cerebellar and sham. The effect of tDCS on postural control was assessed using a sway-referencing paradigm, which induced platform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 69 publications
(101 reference statements)
6
28
1
2
Order By: Relevance
“…In line with the present findings regarding the effects of cerebellar stimulation on balance, other studies showed that a-tDCS of the cerebellum could improve stability parameters in AP and ML directions (8), peak-to-peak sway amplitude, and mean power frequency of sways (7) in older adults. Some motor and cognitive disorders in older adults are associated with age-related changes in the cerebellum (17).…”
Section: Effect Of Cerebellar Tdcs On Balancesupporting
confidence: 92%
See 4 more Smart Citations
“…In line with the present findings regarding the effects of cerebellar stimulation on balance, other studies showed that a-tDCS of the cerebellum could improve stability parameters in AP and ML directions (8), peak-to-peak sway amplitude, and mean power frequency of sways (7) in older adults. Some motor and cognitive disorders in older adults are associated with age-related changes in the cerebellum (17).…”
Section: Effect Of Cerebellar Tdcs On Balancesupporting
confidence: 92%
“…The present findings also showed that a-tDCS of M1 could improve balance in older adults. Similarly, Craig and Doumas (7) found that M1 stimulation had positive effects on the sway amplitude of older adults. In line with studies on older adults, it was reported that M1 facilitation could improve balance in young adults (7,30,31) and patients with Parkinson's disease (32), chronic low back pain (33), and stroke (34).…”
Section: Effect Of M1 Tdcs On Balancementioning
confidence: 77%
See 3 more Smart Citations